PANIC BUYING FACTORS AMONG MALAYSIAN HOUSEHOLDS DURING FIRST PHASE OF MOVEMENT CONTROL ORDER - Nur Amira Mat Rodhi; Sanizah Ahmad; Siti Aisyah Hamali (International Journal of Accounting, Finance and Business, 2022)
The coronavirus epidemic also known as COVID-19 had posed major public healthand governance concerns worldwide including Malaysia. To break the chain of COVID-19,lockdowns are implemented in many places with the Malaysian government imposing aMovement Control Order (MCO), igniting fear and panic buying among consumers. Theobjectives of this study are first, to determine the contributing factors that influence the type ofgoods during panic buying and then to identify the significant factors that contribute to panicbuying. This study used secondary data based on a questionnaire given to 300 respondentsamong Malaysian households. Principal component analysis extracted two main components,named as basic needs and other needs. By comparing the mean of these two components, basicneeds are found to be the most important factor that contributes to panic buying. Next, binarylogistic regression analysis is compared between forward and backward selection method withbackward selection method as best model due to the lower AIC value. Only two significantvariables among Malaysian households are involved in panic buying; they are young adultsand the B40 groups. These findings on consumers’ panic buying behaviours during COVID-19pandemic may give a better understanding and managerial insights for retailers and policymakers.